1978
DOI: 10.1259/0007-1285-51-611-879
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen and radiotherapy: a Medical Research Council trial in carcinoma of the cervix

Abstract: In a randomized controlled clinical trial of hyperbaric oxygen in the radiotherapy of advanced carcinoma of the uterine cervix a total of 320 cases were contributed by four radiotherapy centres in the United Kingdom. The use of hyperbaric oxygen resulted in improved local control and survival. The benefit was greatest in patients under the age of 55 who presented with stage III disease. There was a slight increase in radiation morbidity but it seemed that the benefit of hyperbaric oxygen outweighed this increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(37 citation statements)
references
References 0 publications
1
32
0
2
Order By: Relevance
“…The previous combined method was a repetitive administration of irradiation during HBO exposure. In some clinical trials, significant improvements in local control and survival have been seen in cancers of head and neck, cervical region and uterine cervix (Henk et al, 1977;Watson et al, 1978;Henk, 1986), but no benefit has been demonstrated in patients with cancers of skin, bronchus and bladder (Sealy et al, 1974;Cade and McEwen, 1978). There are only two reports of human malignant gliomas treated with this therapeutic method (Chang, 1977;Dowling et al, 1992).…”
Section: Radiation During Hbo Exposurementioning
confidence: 99%
“…The previous combined method was a repetitive administration of irradiation during HBO exposure. In some clinical trials, significant improvements in local control and survival have been seen in cancers of head and neck, cervical region and uterine cervix (Henk et al, 1977;Watson et al, 1978;Henk, 1986), but no benefit has been demonstrated in patients with cancers of skin, bronchus and bladder (Sealy et al, 1974;Cade and McEwen, 1978). There are only two reports of human malignant gliomas treated with this therapeutic method (Chang, 1977;Dowling et al, 1992).…”
Section: Radiation During Hbo Exposurementioning
confidence: 99%
“…A meta-analysis of over 10,000 patients enrolled in nearly 90 randomized trials over the past 40 years revealed an OR of 0.77 in favor of hypoxia modification strategies (9). Phase III trials have been conducted utilizing radiotherapy with or without (i) increasing oxygen delivery with hyperbaric oxygen (10,11) or carbogen breathing with nicotinamide (12); (ii) the hypoxic cytotoxin, tirapazamine (13,14). Evofosfamide, another hypoxic cytotoxin, was found to yield improved survival in a randomized phase II trial when combined with gemcitabine in patients with pancreatic cancer (15).…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%
“…Minchinton, R.E. Durand There is unequivocal evidence for the presence of radiobiologically hypoxic cells in experimental tumours (Moulder & Rockwell, 1984;Vaupel, 1979) and sound clinical evidence that they play an important role in determining the sensitivity to radiotherapy of some human tumours (Bush et al, 1978;Dische et al, 1983;Henk, 1986, Overgaard et al, 1986Watson et al, 1978). In addition, several studies indicate that sub-populations within tumours exhibit differential sensitivity to chemotherapeutic agents as a result of inherent sensitivity differences between aerobic and hypoxic cells (Teicher et al, 1981) and drug penetration problems (Kerr & Kaye, 1987).…”
mentioning
confidence: 99%